Lost Highway Not Forgotten: Satellite Tracking of a Bowhead Whale (Balaena mysticetus) from the Critically Endangered Spitsbergen Stock - Lydersen, Christian; Freitas, Carla; Wiig, Øystein; Bachmann, Lutz; Heide-Jørgensen, Mads Peter; Swift, René; Kovacs, Kit M. (ARCTIC, 2012)
The Spitsbergen bowhead whale stock is critically endangered. It is believed to number in the tens. Here we report results from the first satellite transmitter ever deployed on an individual from this stock. A female whale was tagged on 3 April 2010 (at 79˚54' N, 01˚03' E), but no locations were transmitted by the tag until 30 April 2010, after which data were received continuously for 86 days. Additionally, three small clusters of locations were transmitted later in the year; the latest was received 20 December 2010 (262 days after deployment). During the 86 days of continuous tracking, the whale initially remained in the middle of the Fram Strait, between 77˚45' N, 5˚ W and 80˚10' N, 5˚ E. For a two-week period starting around 10 June 2010, the whale traveled southwest down to 73˚40' N (at least 950 km). Subsequently it remained at southern latitudes between ~70˚ and 73˚ N until the tag stopped continuous transmissions on 24 July. Movement patterns analyzed using first-passage times (FTP), fitted as functions of various environmental variables using Cox Proportional Hazards models, showed that the whale spent most of its time in waters close to the ice edge with modest ice coverage, over areas where the bottom slope was relatively steep. Winter positions (27 November – 20 December 2010) revealed that the whale was back in the North at about 80˚ N. This information, in combination with recent data from passive acoustic listening devices, suggests that the Spitsbergen bowhead stock overwinters at high-latitude locations. The north-south movements of this whale during summer are consistent with the patterns that early whalers described for bowhead whales in this region in the 16th and 17th centuries. La population de baleines boréales de Spitzberg est en danger critique d’extinction. L’on croit qu’elle se chiffrerait dans la dizaine. Ici, nous faisons état des résultats obtenus à l’aide du premier émetteur satellite à n’avoir jamais été installé sur un individu de cette population. Une baleine femelle a été ...